Initial Segment Differentiation Begins During a Critical Window and Is Dependent upon Lumicrine Factors and SRC Proto-Oncogene (SRC) in the Mouse - Xu, Bingfang (Biol Reprod, 2016)
Without a fully developed and functioning initial segment, the most proximal region of the epididymis, male infertility results. Therefore, it is important to understand the development of the initial segment. During postnatal development of the epididymis, many cellular processes of the initial segment are regulated by lumicrine factors, which are produced by the testis and enter the epididymis with testicular luminal fluid. In this report, we showed that prior to Postnatal Day 15 (P15), the initial segment was lumicrine factor independent in the mouse. However, from P19 onward, lumicrine factors were essential for the proliferation and survival of initial segment epithelial cells. Therefore, P15 to P19 was a critical window that established the dependency of lumicrine factors in the initial segment epithelium. The initial segment-specific kinase activity profile, a marker of initial segment differentiation, was also established during this window. The SFK (SRC proto-oncogene family kinases), ERK pathway (known as the RAF/MEK/ERK pathway) components, and AMPK (AMP-activated protein kinases) pathway components had increased activities from P15 to P19, suggesting that lumicrine factors regulated SFK/ERK/AMPK signaling to initiate differentiation of the initial segment from P15 to P19. Compared with litter mate controls, juvenile Src null mice displayed lower levels of MAPK3/1 (mitogen-activated protein kinase 3/1) activity and a reduced level of differentiation in the initial segment epithelium, a similar phenotype resulting from inhibition of SRC activity within the window of P15 to P19. Therefore, lumicrine factor-dependent SRC activity signaling through MAPK3/1 is important for the initiation of initial segment differentiation during a critical window of development.